Proceedings of the 3rd Annual International Conference on Advanced Material Engineering (AME 2017) 2017
DOI: 10.2991/ame-17.2017.57
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Bending Properties of Lattice Sandwich Structure for Wooden Truss

Abstract: Abstract. Based on an internally interlinked concept of space design, poplar LVL and oriented strand board (OSB) as panel respectively and mongolica sawn timber as truss member, gluing approach is adopted to combine truss members into single truss for core structure in this paper. There are four categories of prepared lattice sandwich structure of wooden truss, including lattice sandwich structure of poplar veneer synclastic truss, lattice sandwich structure of poplar veneer incongruous truss, lattice sandwich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Core geometry parameters were considered as one of the main factors which effect the maximum temperature of the heat source. Wang and Hu 4 investigated the bending properties of lattice sandwich structure with wooden truss by three-point bending method. The study found that lattice sandwich structure with poplar veneer truss has superior bending performance to oriented strand board truss.…”
Section: Typical Core Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Core geometry parameters were considered as one of the main factors which effect the maximum temperature of the heat source. Wang and Hu 4 investigated the bending properties of lattice sandwich structure with wooden truss by three-point bending method. The study found that lattice sandwich structure with poplar veneer truss has superior bending performance to oriented strand board truss.…”
Section: Typical Core Structuresmentioning
confidence: 99%
“…The facings of sandwich structures are relatively thinner than core and seldom exceed several millimeters, while the thickness of the core may be over 50 mm. In order to obtain good mechanical performance, sandwich structure typically has stiff facings (such as aluminum alloys, 1 fiber-reinforced polymer (FRP), 2 and carbon/epoxy prepreg 3 ) and lightweight core (such as processed woods, 4,5 metals, 6 10 and polymers 11 17 ). The facing–core interface is the weakest part of the sandwich structure.…”
Section: Introductionmentioning
confidence: 99%